PENINGKATAN MOTIVASI DAN HASIL BELAJAR IPA DENGAN MODEL PEMBELAJARAN KOOPERATIF TIPE INSIDE OUTSIDE CIRCLE SISWA KELAS VIII E MTS NEGERI SLEMAN KOTA YOGYAKARTA - Agus Prihatin; Astuti Wijayanti (Universitas Sarjanawiyata Tamansiswa, 2017)
This research was aimed to improve motivation and evaluation of science for grade VIII E students through a type of cooperative learning model Inside Outside Circle at MTs Negeri Sleman Kota Yogyakarta. This research is Classroom Action Research that was collaboratively. The subject of this study is 33 students in class VIII E at MTs Negeri Sleman Kota Yogyakarta. Thr object of this study is teaching by using a type of cooperative learning model Inside Outside Circle, motivation, and students evaluation. The collecting data method used observation, documentation, questionnaire, and test. The result of this research showed that after implementing a type of cooperative learning model Inside Outside Circle, motivation and evaluation grade VIII E students became better and improved. This showed that by improvement of average percentage of learning motivation for each cycle, indicator average of motivation pra cycle is 66,84% improve become 75,08% in cycle I and 81,14% in cycle II. The average of evaluation in cycle I am 73 become 79 in cycle II. A lot of students can reach the KKM in cycle I am 17 students with 50% percentage. In the cycle, II become 71,8% one 23 students can reach KKM. Based on the result of the research, the writer gave advice for the science teacher to implement a type of cooperative learning model Inside Outside Circle as the innovation of teaching and cooperative learning model.